Persepsi Remaja Terhadap Kehamilan Diluar Nikah dalam Film Dua Garis Biru - Muhamad Nurul Huda; Veranus Sidharta Pass P (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study examines adolescents' perceptions of the representation of premarital pregnancy in the film Dua Garis Biru (Two Blue Lines), and its impact on their views on relationships, responsibility, and moral values. Film is positioned as a mass communication medium capable of shaping public opinion and effectively conveying social messages, particularly to adolescents. The approach used was a qualitative reception study method, involving eight adolescent informants as the main participants. Data collection techniques were conducted through in-depth interviews, then analyzed using thematic coding using NVivo software, to identify patterns of perception and meaning that emerged from participant responses. The results showed that most adolescents viewed Dua Garis Biru as an educational film that portrayed the realities of adolescent life honestly and touchingly. The film was deemed successful in conveying messages about the importance of responsibility, self-control, and awareness of the consequences of premarital relationships. Furthermore, an understanding of the need for open sexual education and healthy communication between children and parents emerged. The adolescents also highlighted the representation of gender inequality and the greater social pressures felt by women in situations of premarital pregnancy. The film was considered not only entertainment, but also a learning medium capable of shaping adolescents' emotional, moral, and social awareness. The film's reflective and contextual storytelling encourages young audiences to better understand the social realities around them. Thus, Dua Garis Biru (Two Blue Lines) makes a significant contribution in conveying social and moral educational values to adolescents.